Complete mitochondrial genome sequences from five Eimeria species (Apicomplexa; Coccidia; Eimeriidae) infecting domestic turkeys - Ogedengbe, Mosun E (Parasit Vectors, 2014)
BACKGROUND: Clinical and subclinical coccidiosis is cosmopolitan and inflicts significant losses to the poultry industry globally. Seven named Eimeria species are responsible for coccidiosis in turkeys: Eimeria dispersa; Eimeria meleagrimitis; Eimeria gallopavonis; Eimeria meleagridis; Eimeria adenoeides; Eimeria innocua; and, Eimeria subrotunda. Although attempts have been made to characterize these parasites molecularly at the nuclear 18S rDNA and ITS loci, the maternally-derived and mitotically replicating mitochondrial genome may be more suited for species level molecular work; however, only limited sequence data are available for Eimeria spp. infecting turkeys. The purpose of this study was to sequence and annotate the complete mitochondrial genomes from 5 Eimeria species that commonly infect the domestic turkey (Meleagris gallopavo). METHODS: Six single-oocyst derived cultures of five Eimeria species infecting turkeys were PCR-amplified and sequenced completely prior to detailed annotation. Resulting sequences were aligned and used in phylogenetic analyses (BI, ML, and MP) that included complete mitochondrial genomes from 16 Eimeria species or concatenated CDS sequences from each genome. RESULTS: Complete mitochondrial genome sequences were obtained for Eimeria adenoeides Guelph, 6211 bp; Eimeria dispersa Briston, 6238 bp; Eimeria meleagridis USAR97-01, 6212 bp; Eimeria meleagrimitis USMN08-01, 6165 bp; Eimeria gallopavonis Weybridge, 6215 bp; and Eimeria gallopavonis USKS06-01, 6215 bp). The order, orientation and CDS lengths of the three protein coding genes (COI, COIII and CytB) as well as rDNA fragments encoding ribosomal large and small subunit rRNA were conserved among all sequences. Pairwise sequence identities between species ranged from 88.1% to 98.2%; sequence variability was concentrated within CDS or between rDNA fragments (where indels were common). No phylogenetic reconstruction supported monophyly of Eimeria species infecting turkeys; Eimeria dispersa may have arisen via host switching from another avian host. Phylogenetic analyses suggest E. necatrix and E. tenella are related distantly to other Eimeria of chickens. CONCLUSIONS: Mitochondrial genomes of Eimeria species sequenced to date are highly conserved with regard to gene content and structure. Nonetheless, complete mitochondrial genome sequences and, particularly the three CDS, possess sufficient sequence variability for differentiating Eimeria species of poultry. The mitochondrial genome sequences are highly suited for molecular diagnostics and phylogenetics of coccidia and, potentially, genetic markers for molecular epidemiology.